Engaging with spontaneous anthropologies: Fieldwork learning practices across the Greek-Albanian border - Pusceddu, A.M. (2022)
This paper reflects upon the relevance of spontaneous anthropologies for the ways anthropological knowledge is produced and circulated, understood, and made relevant in teaching settings and for the broader public audience. Inspired by Antonio Gramsci’s observations on spontaneous philosophy and common sense, I consider spontaneous anthropologies the conceptions and views –often fragmentary and contradictory –through which people make sense of the world they live in and act upon. Arguably, spontaneous anthropology provides the rough empirical materials for more analytical understandings and explanations of the social and cultural worlds investigated by anthropologists. Drawing from my own research experience with Greek and Albanian border populations, I discuss the relationship between anthropology and spontaneous anthropologies in fieldwork learning practices. I suggest that closer engagements with spontaneous anthropologies in and across national borders can offer a fruitful basis for strengthening both teaching practices and critical anthropological interventions in the public sphere.